Pengaruh Good Corporate Governance Dan Kinerja Lingkungan Terhadap Pengungkapan Lingkungan - Wiwi Hawin Sari; Henri Agustin; Erly Mulyani (Universitas Negeri Padang, 2019)
This research aims to provide empirically the effect of good corporate governance and environmental performance on environmental disclosures. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. Environmental disclosure variables are measured by scores using the Indonesian Environmental Reporting Index (IER) which consists of 35 disclosure items. The sample in this study was determined by purposive sampling method. The type of data used is secondary data obtained from www.idx.co.id as well as company websites and other sites related to research. The analytical method used is Multiple Regression Analysis. The results of this study indicate that environmental performance has a significant positive effect on environmental disclosure, Institutional Ownership has no effect on environmental disclosure and the proportion of independent audit committees also has no effect on environmental disclosures